In-situ sol-gel generation of SiO₂ nanoparticles inside polyamide membrane for enhanced nanofiltration - Li, Jian (2022)
Interfacial polymerization (IP) has been deemed as the principal strategy to fabricate thin film composite (TFC) nanofiltration (NF) membranes. However, the separation performances of TFC membrane are prone to be impaired with the issue of trade-off relationship between selectivity and permeability. Herein, a combined IP and in-situ sol-gel method was proposed to synthesis novel thin film nanocomposite (TFN) NF membrane. The nano-enhanced polyamide (PA) functional layer was created by the IP reaction, while the in-situ generated silicon dioxide (SiO2) nanoparticles were formed through the hydrolysis and condensation process. The optimal separation performance was obtained by tailoring the formation process of SiO2 nanoparticles via varying the NaOH concentration. The results revealed that the in-situ generated SiO2 nanoparticles were uniformly distributed within the PA layer, which greatly enhanced the hydrophilicity due to the abundant Si-OH groups. The membrane decorated by 1 ml TEOS under 0.3 wt% NaOH condition possessed a pure water permeability up to 70.69 L m−2 h−1 bar−1 and high rejection rates against dyes (99.99 % for Congo red, 99.55 % for Coomassie blue G-250, 99.39 % for Reactive blue 19), while maintaining low salt rejections (4.92 % for NaCl, 7.14 % for Na2SO4). Meanwhile, the membrane presented an excellent long-term operational stability.